(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: It is important to evaluate dental students' knowledge, attitudes, perception toward COVID-19 infection control guidelines and its impact on their work.Methods: A cross-sectional study using an online-questionnaire included fifteen statements to assess awareness and knowledge about COVID-19 clinical manifestations and infection control practice protocols among dental students at Sinai University, Egypt. The response of participants to each statement was collected using Likert scale.Results: 486 participants completed the questionnaire-based survey. 75.72% of them had knowledge about the disease contagiousness, 85.98% knew about the symptoms of COVID-19, 91.77% recognized the actual incubation period of the disease, and 47.41% could identify those wild mammals like bats are the possible source of COVID-19, while 68.67% were aware of the spread of virus transmission through interpersonal contacts. 432(88.9%) responders were aware of the infection control guidelines, moreover, they know the ways to prevent the spreading of the virus. 423(87%) responders perceived that dentists are at higher risk than other healthcare professionals. 79.38% of participants gained their information about COVID-19 through social media.Conclusion: North Sinai dental students had a correctitude amount of knowledge, with positive awareness about COVID-19. Government must emphasize the role of social media to spread accurate COVID-19 awareness campaigns.